The giant escape neurons of crayfish: Past discoveries and present opportunities - Herberholz, Jens (Frontiers in Physiology, 2022)
Crayfish are equipped with two prominent neural circuits that control rapid, stereotyped escape behaviors. Central to these circuits are bilateral pairs of giant neurons that transverse the nervous system and generate escape tail-flips in opposite directions away from threatening stimuli.